2016
DOI: 10.1177/0363546516645531
|View full text |Cite
|
Sign up to set email alerts
|

The ACL Graft Has Different Cross-sectional Dimensions Compared With the Native ACL

Abstract: Native ACLs have a smaller cross-sectional area, are "flatter," and experience less incidence of impingement compared with anatomically placed BPTB ACL grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 28 publications
2
27
1
Order By: Relevance
“…Similar to previously reported clinical observations, 31 , 56 the reconstructed grafts in pigs had a substantially bigger cross-sectional area at the midsubstance of the ligament (mean, 147%) when compared with intact ACLs of the contralateral knee. Our regression analysis showed that the grafts with bigger deviations from the cross-sectional area of the native ACL resulted in greater cartilage damage across the tibiofemoral joint.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to previously reported clinical observations, 31 , 56 the reconstructed grafts in pigs had a substantially bigger cross-sectional area at the midsubstance of the ligament (mean, 147%) when compared with intact ACLs of the contralateral knee. Our regression analysis showed that the grafts with bigger deviations from the cross-sectional area of the native ACL resulted in greater cartilage damage across the tibiofemoral joint.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the risk of graft impingement must be taken into consideration when selecting the ACL graft diameter. 28…”
Section: Discussionmentioning
confidence: 99%
“…This has been suggested by other authors. Thein et al 34 evaluated the 3-dimensional shape and cross-sectional area of the native ACL versus the ACL graft and compared the impingement against the femoral notch and PCL, using the bilateral knee MRI of 27 patients with unilateral bone-patellar tendon-bone ACLR. They indicated that 19 operated knees (70%) showed contact or impingement between the ACL graft and the femoral notch as compared with zero knees with a native ACL.…”
Section: Discussionmentioning
confidence: 99%